We are not one people secession and separatism in American politics since 1776 - Lee, Michael J. 1979-; Atchison, R. Jarrod 1979- (Oxford University Press, 2022)
Bands, bonds, and affections -- Secession all the way down : libertarians opt out -- "A slave republic" : secession and southern slavery -- White devils and Black separatists -- "Dykes first" : lesbian separatism in America -- Exodus as secession : achieving God's terrestrial kingdom
Includes bibliographical references and index
Keywords: Geschichte 1776-2022; Autonomiebewegung; Separatismus; Sezession -- Völkerrecht; Unabhängigkeitsbewegung; USA; Secession / United States / History; Separatist movements; National characteristics, American; Political culture / United States; United States / Politics and government; United States / History / Autonomy and independence movements